Least action description of spontaneous fission in fermium and nobelium nuclei based on the Gogny energy density functional - R. Rodríguez-Guzmán; L. M. Robledo (My University, 2018)
The systematic of the spontaneous fission half‑lives for the nuclei ^242–^262Fm and ^250–^260No is analyzed using a least action framework with the Gogny‑D1M parametrization of the energy density functional. The constrained Hartree–Fock–Bogoliubov (HFB) method is used to compute deformed mean-field configurations, zero‑point quantum corrections, and collective inertias. Minimization of the Wentzel–Kramers–Brillouin action is performed in terms of pairing fluctuations, showing that dynamic (least‑action) paths involve enhanced pairing correlations compared to static energy-minimized configurations. This results in spontaneous fission half‑lives several orders of magnitude shorter and in much better agreement with experimental data.
Keywords: spontaneous fission; least action; Gogny D1M energy density functional; pairing fluctuations; fermium; nobelium